State-to-state dissociative photoionization of molecular nitrogen: the full story. Issue 1 (1st January 2020) - Ayari, T.; Desouter-Lecomte, M.; Linguerri, R.; Garcia, G. A.; Nahon, L.; Ben Houria, A.; Ghalila, H.; Ben Said, R.; Hochlaf, M.
ABSTRACT: N2 is a major constituent of Earth and planetary atmospheres. First, evidenced in 1952, the dissociative photoionization of molecular nitrogen, N2, plays an important role in the species abundance, out of equilibrium evolution, and chemical reactivity of diverse media including upper atmospheres (the so-called ionospheres) and plasma. Many scenarios were proposed for rationalizing the dissociative ionization mechanisms and exit channels, which are reviewed here, mainly involving the N2 + (C 2 ∑u +, v + ) vibrational levels state-to-state dynamics on which we focus. We show, however, that previous studies are not comprehensive enough for fully shedding light on the complex undergoing processes. As a complementary global work, we used state-of-the-art quantum chemistry, time dependent and independent theoretical approaches associated to advanced experimental techniques to study the unimolecular decomposition of the N2 + ions forming the N + + N products. In addition to the already suggested spin-orbit-induced predissociation of the cationic C 2 ∑u + state, we documented a new mechanism based on vibronic coupling and tunneling dissociation. Besides, the quantum processes highlighted here should be also in action in the dynamics of electronically excited larger molecular systems involved in physical and chemical phenomena in plasma and in various natural environments on Earth and beyond. Graphical abstract: